Business-To-Business E-Commerce with Open Buying On the Internet - Fatema Khan, Almas; Mulchandani, Mona (International Journal of Computer Sciences and Engineering, 2025)
Internet based e-Commerce is flourishing, but mostly in the Business-to-Consumer world. The lack of well- accepted standards is hindering the success in promoting Business-to-Business e-Commerce solutions. Open Buying on the Internet standard is one of the promising efforts in bringing business-to- business e-Commerce into corporate purchasing. Today we have various options to buy a product online but sometime we pay more than the price of product and we found similar products in local market in less price. The only difficulty is to search for the product in local market. The only option is to visit each and every shop in local market to buy a particular product. Buying products online sometime leads as to very bad shopping experience and we face many problems related to return policy provided by the seller but buying from local market is something leads us to a good hands on experience on the products and its demo so we don‟t have to worry about product quality The plus point of local market purchasing is „Bargain‟. The only thing is matter is we have to search a lot for buying a product from local market because there are no way where we get all the details in one place. To overcome this problem we provide a solution where local seller show their products and details in category wise and user browse through it and then purchase it from the shop by visiting it.